The Role of Visual Narratives in Representing Female Identity and Emotions in Little Women (2019) - E. C. Monteverdi (Art and Society, 2024)
This paper explores the role of visual narratives in representing female identity and emotions in Greta Gerwig’s Little Women (2019). Through an analysis of key cinematic techniques, including nonlinear storytelling, costume design, spatial dynamics, cinematography, and visual metaphors, the study examines how these elements enrich the portrayal of the March sisters’ individuality and collective experiences. The nonlinear structure, marked by contrasting color palettes, juxtaposes the innocence of youth with the challenges of adulthood, reflecting the emotional and psychological evolution of the protagonists. Costume design highlights the distinct personalities and aspirations of Jo, Amy, Meg, and Beth, while spatial dynamics underscore the tension between freedom and societal constraints. Cinematographic techniques, such as close-ups and framing, capture moments of intimacy and creativity, deepening emotional resonance. Finally, visual metaphors—ranging from Jo’s manuscripts to Beth’s piano—symbolize empowerment and the sisters’ pursuit of self-determination. This paper argues that Gerwig’s adaptation transforms a literary classic into a profound visual narrative, celebrating the complexities of female identity and emotional resilience while maintaining timeless relevance.